2009
DOI: 10.1016/j.ijgo.2008.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Reducing maternal mortality among Afghan refugees in Pakistan

Abstract: Objective: The International Rescue Committee (IRC) strove to reduce maternal mortality among Afghan refugees in Hangu district of Pakistan by improving access to emergency obstetric care (EmOC), community knowledge of danger signs of pregnancy, and the use of health information. Methods: IRC established EmOC centers, trained community members on safe motherhood, linked primary health care with education on danger signs of pregnancy and the importance of skilled attendance, and improved the health information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(75 citation statements)
references
References 3 publications
0
75
0
Order By: Relevance
“…Awareness of the danger signs and symptoms of pregnancy complication should help women make timely decisions about medical care [4,10,14,20]. A considerable proportion of women enrolled in the present study (84.9%) recognized fewer than 4 danger signs of serious pregnancy complications, and 38.8% could not name any of these signs and symptoms.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Awareness of the danger signs and symptoms of pregnancy complication should help women make timely decisions about medical care [4,10,14,20]. A considerable proportion of women enrolled in the present study (84.9%) recognized fewer than 4 danger signs of serious pregnancy complications, and 38.8% could not name any of these signs and symptoms.…”
Section: Discussionmentioning
confidence: 83%
“…This failure may lead to delayed decision in seeking care, which is reported to be a contributing factor in 30%-77% of all maternal deaths [8,9]. Studies indicate that education about pregnancy danger signs and symptoms targeting healthcare providers at different levels, as well as women of reproductive age, increased awareness and recognition of complications, motivated women to seek timely support, and improved referral to health services [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing maternal knowledge among refugee women, especially recognition of danger signs beyond abdominal pain and headaches, could improve care seeking and thus birth outcomes [6,21,22]. A study of Afghan refugees showed that providing information on danger signs in pregnancy increased timely seeking of skilled birth support [23]. A possible reason for better knowledge transmission in the Afghan study was the higher number of educational workers serving a smaller population, with 330 volunteer community health workers and 325 female health workers for 96,300 male and female refugees (1:300) versus 75 facilitators for 125,000 female refugees (1:1,700) in Guinea [12,23].…”
Section: Discussionmentioning
confidence: 99%
“…A study of Afghan refugees showed that providing information on danger signs in pregnancy increased timely seeking of skilled birth support [23]. A possible reason for better knowledge transmission in the Afghan study was the higher number of educational workers serving a smaller population, with 330 volunteer community health workers and 325 female health workers for 96,300 male and female refugees (1:300) versus 75 facilitators for 125,000 female refugees (1:1,700) in Guinea [12,23]. This suggests that observable increases in maternal knowledge and attitudes require considerable staff investment.…”
Section: Discussionmentioning
confidence: 99%
“…The international Rescue Committee has provided maternity care in camps for Afghan refugees in Pakistan for 20 years and gained the trust and participation of their clients as measured by the uptake of services [2]. When the article from Yemen was submitted, it described only the results of a needs assessment-a sad story indeed, with few obstetric services being provided [3].…”
mentioning
confidence: 99%